A Qualitative Appraisal of Neurotology Fellowship Websites. Issue 10 (December 2020) - Hakimi, Amir A.; Loanzon, Roberto S.; Azhdam, Ariel M.; Liu, Yuan; Simental, Alfred
Abstract : Objective: To assess the accessibility and breadth of online information regarding neurotology fellowship programs by appraising individual fellowship websites as well as two popular online databases. Methods: The American Neurotology Society Program Information Page (ANSPIP), the American Medical Association's Fellowship and Residency Electronic Interactive Database (FREIDA), and three online search engines (Google, Yahoo, Bing) were assessed for accessibility to individual fellowship websites. Each program's ANSPIP data sheet and fellowship-specific website were then evaluated for the presence of 18 characteristics of interest to the neurotology fellowship applicant. Results: All three search engines yielded 23 (96%) Accreditation Council for Graduate Medical Education (ACGME)-accredited neurotology fellowship websites. Searching "Neurotology fellowships" in Google, Yahoo, and Bing required exploring up to nine pages of search results to identify all of the ACGME-accredited program-specific websites. Direct links to program websites were found on 12 (55%) and 3 (13%) of the ANSPIP and FREIDA fellowship pages, respectively. Of the 18 characteristics of interest, the ANSPIP data sheet and individual program websites on average delineated 8.0 and 7.8 characteristics, respectively. Ninety-one percent of fellowship websites included program coordinator information, general program description, and breadth of surgical exposure. In contrast, work/life balance, postfellowship placement, and current fellow(s) were least commonly displayed (4%, 9%, 13% respectively). One-hundred percent of ANSPIP data sheets included program coordinator information, number of fellows, and affiliated hospital(s), whereas none of the pages included selection criteria, application requirements, description of location, or work/life balance. Conclusion: Although most neurotology fellowship programs have websites or ANSPIP data sheets, many of them lack information that has been previously demonstrated to be valued by applicants. Furthermore, incongruence of information between these sources may lead to confusion, applicant stress, and reflect poorly on fellowship programs. Perhaps a standardized list of ACGME-required data points to be posted on websites would facilitate the application process.